A general theory of domination and justice - Lovett, Frank (Oxford : Oxford University Press, 2010)
This study builds on the work of contemporary civic republicans supplying a detailed analysis of the concept of domination absent in the familiar accounts of political freedom as non-domination.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Power (Social sciences); Social control; Social justice